Identification and characterization of a minisatellite contained within a novel miniature inverted-repeat transposable element (MITE) of Porphyromonas gingivalis. Issue 1 (December 2015) - Klein, Brian; Chen, Tsute; Scott, Jodie; Koenigsberg, Andrea; Duncan, Margaret; Hu, Linden
Abstract Background Repetitive regions of DNA and transposable elements have been found to constitute large percentages of eukaryotic and prokaryotic genomes. Such elements are known to be involved in transcriptional regulation, host-pathogen interactions and genome evolution. Results We identified a minisatellite contained within a miniature inverted-repeat transposable element (MITE) inPorphyromonas gingivalis . TheP. gingivalis minisatellite and associated MITE, named 'BrickBuilt', comprises a tandemly repeating twenty-three nucleotide DNA sequence lacking spacer regions between repeats, and with flanking 'leader' and 'tail' subunits that include small inverted-repeat ends. Forms of the BrickBuilt MITE are found 19 times in the genome ofP. gingivalis strain ATCC 33277, and also multiple times within the strains W83, TDC60, HG66 and JCVI SC001. BrickBuilt is always located intergenically ranging between 49 and 591 nucleotides from the nearest upstream and downstream coding sequences. Segments of BrickBuilt contain promoter elements with bidirectional transcription capabilities. Conclusions We performed a bioinformatic analysis of BrickBuilt utilizing existing whole genome sequencing, microarray and RNAseq data, as well as performingin vitro promoter probe assays to determine potential roles, mechanisms and regulation of the expression of these elements and their affect on surrounding loci. The multiplicity, localization and limited host range nature of MITEs and MITE-like elements inP. gingivalis suggest that these elements may play an important role in facilitating genome evolution as well as modulating the transcriptional regulatory system.